Breaking Stalin's nose - Yelchin, Eugene (New York : Henry Holt, 2011)
In the Stalinist era of the Soviet Union, ten-year-old Sasha idolizes his father, a devoted Communist, but when police take his father away and leave Sasha homeless, he is forced to examine his own perceptions, values, and beliefs.
Keywords: Fathers and sons -- Juvenile fiction; Communism -- Juvenile fiction; Political persecution -- Soviet Union -- Juvenile fiction; Soviet Union -- History -- 1925-1953 -- Juvenile fiction; Communism -- Fiction; Political persecution -- Soviet Union -- Fiction; Fathers and sons -- Fiction; Soviet Union -- History -- 1925-1953 -- Fiction; Russia -- History -- 1925-1953 -- Fiction; Communism -- Fiction; Father-son relationship -- Fiction